VALUASI EKONOMI HUTAN MANGROVE DI TANJUNG DUDEPO, KECAMATAN BOLAANG UKI, KABUPATEN BOLAANG MONGONDOW SELATAN - Rey Wahyudi Simbala; Hengki Djemie Walangitan; Charles ., Kepel (AGRI-SOSIOEKONOMI, 2017)
The objectives of the study were to analyze: (1) direct and indirect benefits; and (2) The total economic value of mangrove forests in Dudepo Cape, Bolaang Uki Sub-district, South Bolaang Mongondow Regency, North Sulawesi Province. This research was conducted inside and around the area of mangrove protected forest in Dudepo Cape. The study was conducted for 3 (three) months from January - March of 2016. This research uses primary data and secondary data. Primary data were collected through interviews with the community based on prepared questionnaires. Sampling colection using purposive sampling method. Secondary data were collected including from Bolaang Uki Sub-district Office and Dudepo Village Office. The data collected from the field were analyzed using descriptive and quantitative analysis methods. The study found that (1) the direct benefits earned by the community consisted of the value of forest products and the value of the fishery benefits (the benefits of wood for house construction, the benefits of wood for houses, the benefits of firewood, the benefits of wood for stakes and fences, the benefits of shrimp, and the benefits of crabs). While the value of indirect benefits of abrasion retention and erosion benefits, the benefits of choice, the benefits of existence and inheritance benefits. (2) The total economic value of mangrove forest ecosystem in Dudepo village consists of direct benefit value of Rp. 822,165,000 / year of indirect benefit amount of Rp. 453.792.178 / year, the value of the preferred benefit of Rp. 306.405.000./year, the value of the existence benefit of Rp. 1.372.635 / year, the value of the existence benefit of Rp. 13.353.660 / year. and inheritance value of Rp. 82.216.500 / year. The total economic value of the total benefit of mangrove forest ecosystem in Dudepo village is Rp. 1.677.932.338./ year.